Present Food Shopping Habits in the Spanish Adult Population: A Cross-Sectional Study - Achón, María (Nutrients, 2017)
Information on grocery shopping patterns is one key to understanding dietary changes in recent years in Spain. This report presents an overview of Spanish food shopping patterns in the adult population. A cross-sectional, nationally representative telephone survey was conducted in Spain. Individuals were asked about food shopping responsibility roles, types of visited food stores, time spent, additional behaviors while shopping, the influence of marketing/advertising and, in particular, fresh produce shopping profile. Binary logistic regression models were developed. The final random sample included 2026 respondents aged ≥18 years, of which 1223 were women and 803 were men. Women reported being in charge of most of the food shopping activities. Looking for best prices, more than looking for healthy or sustainable foods, seemed to be a general behavior. Supermarkets were the preferred retail spaces for food price consideration, convenience, variety and availability. Fresh produce shopping was associated with traditional markets and neighborhood stores in terms of reliance and personalized service. It is essential to highlight the importance of the role played by women. They are the main supporters concerned in preserving adequate dietary habits. Economic factors, more than health or food sustainability, are commonly considered by the population. Traditional markets may play an important role in preserving some healthy dietary habits of the Mediterranean food culture in Spain.